Gastric Ischemia after SARS-CoV-2 Infection - Woo Yong Lee; Byung Woo Yoon (Life, 2023)
Gastric ischemia is uncommon because the stomach has multiple collateral blood supplies. The etiology of gastric ischemia is vascular insufficiency caused by systemic hypotension, vasculitis, or disseminated thromboembolism. Mechanical causes include gastric volvulus and acute gastric distention. Uncommon as gastric ischemia is, we are the first to report a 65-year-old male who developed gastric ischemia leading to gastric pneumatosis 26 days after initial treatment for severe acute respiratory syndrome coronavirus-2 infection (SARS-CoV-2), via laparoscopic imaging. We conclude that physicians should be suspicious of gastric ischemia when the patient is infected with SARS-CoV-2 with severe abdominal pain and should proceed with medical conservative care instead of surgery.